Diseño de la red de fibra óptica entre Quito y Guayaquil para el Comando Conjunto de las Fuerzas Armadas - León Albiño, Iván Mauricio (2016)
Telecommunications are now a fundamental to the development of organizations. The advantages that provide scalable, adaptable and reliable communications systems are endless, and its implementation requires among other things, the use of high performance medium transmission such as optical fiber, thus allowing an adequate adaptation and integration of emerging technologies for providing better quality telecommunications services. This project's main objective, is the design of the telecommunications network to interconnect the offices of the Comando Conjunto de las Fuerzas Armadas (COMACO) located in the cities of Quito and Guayaquil using optical fiber as transmission medium for optimizing their existing connections. During it development, it was considered as a priority, to get an optimal future integration with the internal infrastructure to ensure the friendly migration without jeopardizing the proper functioning of all subsystems in the institution. The final design obtained covers a technical analysis of the geographical sections and its respective mathematical calculations to estimate the performance of the network with the respective simulation of the behavior of links using the software OptSim. Additionally, an analysis of the economic feasibility study was conducted to determine the investment costs and recovery time of it in the event that the Comando Conjunto de las Fuerzas Armadas del Ecuador decides to make its implementation. In addition to all the features that stand out in the design of the optical network in terms of speed and capacity of the links, in the transmission processes would apply high levels of security and confidentiality allowing the Fuerzas Armadas of our country manage their information classified reliably.